Narradores hispanoamericanos de hoy : Simposio - Avalle-Arce, Juan Bautista (Book collections on Project MUSE., 2018)
This volume represents the proceedings of the 1973 symposium Narradores hispanoamericanos de hoy, held at the University of North Carolina at Chapel Hill. The works presented offer insights on the work of authors such a s Alfonso Reyes, Julio Cortázar, Miguel Ángel Asturias, Gabriel García Márquez, Manuel Puig, Mario Vargas Llosa, and Severo Sarduy.